1992
DOI: 10.1111/j.1476-5381.1992.tb14525.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential and current responses to neurotensin in the longitudinal muscle of the rectum of the fowl

Abstract: 1The effects of neurotensin (NT) on membrane potential and membrane current of the longitudinal smooth muscle of chicken rectum were investigated by intracellular recording and whole-cell voltage clamp. 2 NT (3 nM-1.2 SAM), when applied via the bathing medium, produced a concentration-dependent membrane depolarization with an EC50 of 18 ± 2 nM (n = 7) which was accompanied by an increase in the membrane conductance. The effect was biphasic: an initial, rapid depolarization reached a peak within 2-3 min and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Further, patch clamp experiments revealed that both ATP and neurotensin are channel activators with specific membrane receptors. Both agents activate current with a reversal potential close to 0 mV in a quasi-physiological ionic environment (Komori et al, 1992b; the present study). Activation of such currents leads to membrane depolarization.…”
Section: Properties Of the A Tp-induced Inward Currentsupporting
confidence: 57%
See 1 more Smart Citation
“…Further, patch clamp experiments revealed that both ATP and neurotensin are channel activators with specific membrane receptors. Both agents activate current with a reversal potential close to 0 mV in a quasi-physiological ionic environment (Komori et al, 1992b; the present study). Activation of such currents leads to membrane depolarization.…”
Section: Properties Of the A Tp-induced Inward Currentsupporting
confidence: 57%
“…Local application of either ATP or neurotensin by means of pressure ejection from micropipettes evokes a brief, monophasic membrane depolarization similar to the ej.p. (Komori & Ohashi, 1988b;Komori et al, 1992b). Further, patch clamp experiments revealed that both ATP and neurotensin are channel activators with specific membrane receptors.…”
Section: Properties Of the A Tp-induced Inward Currentmentioning
confidence: 99%
“…In the gastrointestinal tract, an increasing number of biological effects have been attributed to NTs discovery. The evidence indicates that NTs released from entero-endocrine N cells 22 is involved in slow wave regulation in the gastrointestinal tract and promotes the peristaltic activity of the intestine by acting on NTSR1 11 23 . Although the bladder, which is an urinary organ regulating the storage and elimination of urine, has a physiological function different from the gastrointestinal tract, the urinary tract and gastrointestinal tract share a common mechanism in generating spontaneous myogenic contractions.…”
Section: Discussionmentioning
confidence: 99%
“…New ideas and evidences have emerged regarding the role of NTs in the contraction and pacemaker currents of the small intestine. NTs induces contraction of the small intestine smooth muscle in a concentration-dependent manner via its action on the NTSR1 of SMCs and interstitial cells of Cajal (ICCs) 11 12 . In addition, the relationship between NTs and cholinergic systems has been documented in several research articles.…”
mentioning
confidence: 99%
“…Chicken NT also induces Ca 2+ release from internal store, which is responsible for the contractile activity in the longitudinal smooth muscle of the rectum [24]. In this study, chicken NT induced an increase in intracellular Ca 2+ concentrations in the chicken NTR1-expressing cells.…”
Section: Discussionmentioning
confidence: 92%